Application of desmid diversity in assessing the water quality of 12 freshwater resources in Thailand - N. Ngearnpat (2018)
Desmids from 12 freshwater resources in the northern part of Thailand were investigated during 2002 to 2003. A total of 91 taxa were found. They belonged to 17 genera: Actinotaenium, Spirotaenia, Netrium, Gonatozygon, Pleurotaenium, Closterium, Euastrum, Micrasterias, Cosmarium, Cosmocladium, Stuarastrum, Staurodesmus, Xanthidium, Teilingia, Spondylosium, Hyalotheca and Desmidium. The water qualities in all the water resources were classified as oligotrophic to meso-eutrophic by trophic status. The taxa that could possibly be used as bioindicators of trophic state were Staurastrum gutwinskii, Spondylosium pandurifoemae, Cosmarium capitulum, C. mediosrobiculatum var. egranutum, S. tortum, Closterium gracile var. elongatum, C. kuetzingii and Closterium dianae var. dianae. The most frequently found taxa were Staurastrum limneticum var. burmense, S. tetracerum var. tetraerum, Pleurotaenium trabecula, Closterium ehrenbergii var. ehrenbergii and C. kuetzingii. The rare taxa in this study were Actinotaenium sp. Spirotaenia condensata, Pleurotaenium burmense var. dacchense and Micrasterias apiculata. Forty-one taxa of desmids were identified as new records for Thailand. © 2007 Springer Science+Business Media B.V.